An alternative technique to the demolition of a prestressed concrete box-girder bridge: A case study - S.S.R. Pereira; M.D.C. Magalhaes; H. Gazzinelli (Case Studies in Construction Materials, 2017)
This is a case study in which the partial collapse of a prestressed concrete box-girder bridge in Brazil happened only nine days after removing the supporting scaffolding. It is believed that the actual reinforcement longitudinal steel bars in the pile caps were underestimated. Although only part of the structure had collapsed, it was decided that the whole structure should be demolished. It was claimed that there was not available alternatives for ‘in situ’ structural recovery that would not compromise local traffic and safety precaution procedures. This paper presents an alternative technique for the bridge structural recovery. The application of this technique was possible because the prestressing process used unbonded pos-tensioned concrete, i.e. the sheaths were not filled with grout. The technique was based on the use of a weld torch to cut the tensioned strands in the box-girders methodically, unloading the pillars and foundations. Experimental tests were performed ‘in loco’ and proved to be effective and safe. The application of this suggested technique ‘in situ’ is believed to be an original contribution to the knowledge.